Employee Performance During Remote Work - Marzena OGÓREK; Dominika STRYCHARSKA (Communications of International Proceedings, 2023)
The main aim of the study is to assess the impact remote working as a method of organising work introduced suddenly and on massive scale has on employee performance. The survey is also designed to demonstrate the factors that influence the quality of performed work, and to establish to what extent they translate into performance levels. The study will answer the question: what was the effectiveness of employees right after the introduction of remote work (at the time of organizational and information chaos, general panic)?
Keywords: remote work; employee efficiency; independence